2018
DOI: 10.1136/bmjopen-2017-021256
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a domestic violence and abuse training and support programme in primary care in the real world: updated modelling based on an MRC phase IV observational pragmatic implementation study

Abstract: ObjectivesTo evaluate the cost-effectiveness of the implementation of the Identification and Referral to Improve Safety (IRIS) programme using up-to-date real-world information on costs and effectiveness from routine clinical practice. A Markov model was constructed to estimate mean costs and quality-adjusted life-years (QALYs) of IRIS versus usual care per woman registered at a general practice from a societal and health service perspective with a 10-year time horizon.Design and settingCost–utility analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Informed by the Medical Research Council guidance on evaluating complex interventions (Moore et al, ; MRC, ), we conducted a theory‐based mixed‐method process evaluation of the implementation of IRIS which included: (a) a case study; (b) a survey; (c) qualitative analysis of free‐text comments from the survey; (d) qualitative interviews; (e) document review. This process evaluation was carried out alongside the evaluation of the outcomes (Sohal et al, ) and cost‐effectiveness (Barbosa et al, ). The choice of the theoretical and analytical frameworks, study design and methods were influenced by the complexity of the IRIS intervention, the target audience of people involved in implementation of DVA programmes and the experience of the research team.…”
Section: Methodsmentioning
confidence: 99%
“…Informed by the Medical Research Council guidance on evaluating complex interventions (Moore et al, ; MRC, ), we conducted a theory‐based mixed‐method process evaluation of the implementation of IRIS which included: (a) a case study; (b) a survey; (c) qualitative analysis of free‐text comments from the survey; (d) qualitative interviews; (e) document review. This process evaluation was carried out alongside the evaluation of the outcomes (Sohal et al, ) and cost‐effectiveness (Barbosa et al, ). The choice of the theoretical and analytical frameworks, study design and methods were influenced by the complexity of the IRIS intervention, the target audience of people involved in implementation of DVA programmes and the experience of the research team.…”
Section: Methodsmentioning
confidence: 99%
“…IRIS advocate educator (AE) who receives referrals directly from trained clinicians, sees patients affected by DVA, usually within the practice, dispensing expert advocacy and ensuring direct access for women to specialist abuse services. Women can also self-refer if they see IRIS publicity material displayed within a practice [17].…”
Section: Iris Service Descriptionmentioning
confidence: 99%
“…In our interrupted time series study [17], in two boroughs the provision of IRIS service was disrupted for a period of three and six months respectively. Our research question is whether the service disruption in each borough had an effect on the referral rate, during the period within which the disruption occurred.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Implementation of IRIS outside of a trial [16] resulted in a large increase in referrals received by DVA service providers (3024%; 95%CI=(2055%,4477%)), with no increase in 61 general practices in the fifth borough that did not fund IRIS, but instead provided DVA information sessions to which general practice clinicians were invited [17]. IRIS outside the trial setting is also cost-effective, from the NHS and societal perspective, good value for the NHS, cost saving for society -incremental net monetary benefit was £22 and £42 respectively [18]. A mixed method implementation process evaluation and a qualitative study found that staff mix and IRIS' joined up approach, bridging the planets of general practice and specialist domestic abuse support services is crucial to making IRIS work [19,20].…”
mentioning
confidence: 99%